IFR dan Return On Asset di Indonesia - Muhammad Hamdan Sayadi (ITB AAS INDONESIA, 2023)
This study aims to examine the effect of IFR on return on assets. The sample used is a company in Indonesia that has internet financial statements. Multiple linear regression analysis is used to test research hypotheses. The descriptive statistical results showed minimum and maximum ROA values for 216 IFR companies of -27,700 and 36,360 respectively. While the minimum and maximum values for IFR are (13,000) and (38,000). The results of the regression model of the effect of IFR on ROA showed a significant influence between IFR on ROA with a significant level of 0.005 and a B-coefficient of 0.280. Each increase in IFR by one unit can increase ROA by 0.280. So, it can be concluded that the hypothesis is accepted.